2004
DOI: 10.1165/rcmb.2003-0223oc
|View full text |Cite
|
Sign up to set email alerts
|

Protease-Activated Receptor-2–Mediated Inhibition for Ca2+ Response to Lipopolysaccharide in Guinea Pig Tracheal Epithelial Cells

Abstract: The protease-activated receptor-2 (PAR-2) has been implicated in airway inflammation. Here, we examined the interaction between PAR-2 and lipopolysaccharide (LPS), a major proinflammatory factor, using cultured guinea pig tracheal epithelial cells. In fura2-loaded cells, LPS (1 microg/ml) transiently increased intracellular Ca(2+) concentrations ([Ca(2+)]i), this effect being abolished by a Ca(2+) channel blocker, verapamil, and Ca(2+) removal. Prestimulation of PAR-2 with trypsin (0.1-1 U/ml) or an agonist pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…It is possible that cytochalasin D inhibited hypertrophic cell growth through another mechanism such as reduction of glucose uptake resulting from inhibition of actin polymerization because actin organization has been demonstrated to regulate glucose uptake by modulating glucose transporter trafficking (27). In previous reports using airway epithelial cells, we showed that PAR regulates cytoskeletal structure as well as cell function such as neutrophil adhesion through PKC-and/or Rho-dependent signaling (28,29). Furthermore, it was demonstrated that PKC and RhoA act in concert as mediators of actin cytoskeleton organization (18,30).…”
Section: Discussionmentioning
confidence: 86%
“…It is possible that cytochalasin D inhibited hypertrophic cell growth through another mechanism such as reduction of glucose uptake resulting from inhibition of actin polymerization because actin organization has been demonstrated to regulate glucose uptake by modulating glucose transporter trafficking (27). In previous reports using airway epithelial cells, we showed that PAR regulates cytoskeletal structure as well as cell function such as neutrophil adhesion through PKC-and/or Rho-dependent signaling (28,29). Furthermore, it was demonstrated that PKC and RhoA act in concert as mediators of actin cytoskeleton organization (18,30).…”
Section: Discussionmentioning
confidence: 86%
“…Trypsin is an agonist of PARs, which stimulate an increase in the intracellular concentration of Ca 2ϩ and PKC activation. The activation of PAR receptors has been found to inhibit the Ca 2ϩ response of guinea pig tracheal epithelial cells in culture to LPS (45). Small concentrations of trypsin (1-10 ng/ml) below those that cleave ENaC directly were found to activate ENaC via an indirect, receptor-mediated mechanism (3).…”
Section: Discussionmentioning
confidence: 99%
“…For a long time it was assumed that PRRs were exclusively found on immune cells of hematopoietic origin and, therefore, most of our current information regarding PRR-mediated signal transduction is largely based on these cells [1,47]. Although there is no conclusive data suggesting cell-specific TLR4 signaling, there have been suggestions that LPSs evoke intracellular signaling reactions in Kupffer cells [48] and tracheal epithelial cells [49] that are absent in polymorphonuclear leukocytes [50]. Here, we report the existence of a distinct TLR4-mediated signaling pathway leading to IL-6 secretion that is present in BECs but absent in other human cell types.…”
Section: Discussionmentioning
confidence: 99%